Evaluation of access policies and practices of selected academic archive services in Metro Manila - Varona, Ronie Von L.; Olgado, Benedict S. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2018)
This study evaluated the access policies and practices of seven selected academic archive services in Metro Manila based on the perceived compliance to the standard of the heads of each academic archive service.

The evaluation was done using a survey questionnaire based from the standards set by the Public Services Quality Group, an interest group of the UK National Archives.

The results showed that the academic archives in this study had various levels of perceived compliance to the standard. The percent of perceived compliance to the standard is highly dependent on several factors. These factors include staffing problems, perception of the stakeholders, and the nature of their collection. However, the bigger problem perceived by the researcher is not the access, but the outreach to the users. They are ready to provide access to their collection, but they do not have a lot of users. Getting the users involved in the archive service is a huge challenge for the archive services in this study.
Thesis (Bachelor of Library and Information Science)
Keywords: Archives -- Philippines -- Manila Metropolitan Area